Power supply of internet of things (IoT) - Liew, Dominic Mian Yi (Nanyang Technological University, 2020)
Wearable devices are making significant impact in changing the current healthcare industry. These devices are capable of helping patients read their vital signs and provide warning indication when critical condition was detected. Smart contact lens is growing popular such that even big companies like google have come out with a conceptual lens. This is very convenient for patients with chronic diseases such as diabetes as a smart contact lens can provide non-intrusive methods by the usage of their glucose level. However, much research on smart contact lens uses wireless communication for the transmission of data which requires the use of an external receiver. Hence, electrochromic alarm system is an alternative mode of data transmission, but it requires a power supply system. Existing studies have incorporated lithium ion battery in smart contact lens. However, lithium ion battery is dangerous to be used on the eye as it has a high voltage range. In this project, power supply system with battery using ions in tear and self-charging by solar energy harvesting, would be designed and implemented on the smart contact lens. This will remove the requirement of an external transmitter or receiver used in wireless power supply.